An example of entrepreneurship in women's education: akhism-baciyani rum training in vocational education from past to present - YILMAZ, ALİ (IGI GLOBAL, 2021)
The organization of Akhism (Ahilik) is an example of non-formal education, established on Anatolian soil in the 13th century. With its women's branch—Bajiyan-ı Rum/Bacılık/sisterhood—it aims to educate women professionally and helps women contribute to society. It is expected from women and men to be good and moral individuals, tradesmen, craftsmen, or traders. By doing their jobs well, they managed to achieve economic stability in society. Women were given the opportunity to have entrepreneurial characteristics in the community and to do their best in line with their own abilities. Akhism/Bacılık system affected the Turkish states and education systems established on Anatolian lands. The effect also continues today. In this chapter, which is a literature review, what the Akhism/Bajiyan-ı Rum system is, its place in the vocational education of women, and its effect on today were discussed.